Low energy impact on the short kenaf fibre reinforced epoxy composites: effect to the residual strength and modulus / Syarifah Yunus … [et al.] - Yunus, Syarifah; Abdullah, Abdul Hakim; Abdul Halim, Nurul Hayati; Salleh, Zuraidah; Md. Taib, Yakub (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
In this investigation, the effect of low energy impact to the residual strength and modulus of short kenaf fibre reinforced epoxy composites were investigated. The composites were made from hand lay-out technique and subjected to low impact energy at the 20%, 25% and 30% of impact failure values. The load-time curve exhibited the damage states of unreinforced epoxy specimens and short kenaf fibre reinforced epoxy composites. The research found that the low energy impacts were affecting the residual strength and residual stiffness which indicated the short kenaf fibre reinforced epoxy composites were extremely sensitive to the impact loads. The damages were manifest by the visible observation of cracks on the specimens